STATUTORY INTERPRETATION -- COMPUTER FRAUD AND ABUSE ACT -- NINTH CIRCUIT HOLDS THAT EMPLOYEES' UNAUTHORIZED USE OF ACCESSIBLE INFORMATION DID NOT VIOLATE THE CFAA. -- United States v. Nosal, 676 F.3d 854 (9th Cir. 2012) (en bane). (Harvard Law Review, 2013)
The article discusses the U.S. Court of Appeals for the Ninth Circuit's ruling in the 2012 case United States v. Nosal which deals with a statutory interpretation of the nation's Computer Fraud and Abuse Act, as well as the legal aspects of computer hacking and the transmission of confidential information. Other topics include aiding and abetting, motions to dismiss, and U.S. government charges against former Korn/Ferry International (KFI) executive search firm employee David Nosal.